Rheological Behavior and Strength Characteristics of Cement Paste and Mortar with Fly Ash and Ggbs Admixtures - Saavedra-Flores, E; Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A cement paste or mortar is composed of a mineral skeleton with micron to millimeter-sized grains, surrounded by water filaments. The cohesion or shear resistance in the cement paste and mortar is caused by capillary forces of action. In the case of mortar mixes, there is friction between the particles. Therefore, the mortar mixture shows both friction between particles and cohesion, while the paste shows only cohesion, and the friction between particles is negligible. The property of the cement paste is greatly influenced by the rheological characteristics like cohesion and internal angle friction. It is also interesting that when studying the rheology of fresh concrete, the rheological behavior of cement paste and mortar has direct applicability. In this paper, the rheological characteristics of cement paste and mortar with and without mineral admixtures, that is, fly ash and ground granulated blast-furnace slag (GGBS), were studied. A cement mortar mix with a cement-to-sand ratio of 1:3 was investigated, including fly ash replacement from 10% to 40%, and GGBS from 10% to 70% of the weight of the cement. A suitable blend of fly ash, GGBS, and ordinary Portland cement (OPC) was also selected to determine rheological parameters. For mortar mixtures, the flow table was conducted for workability studies. The flexural and split tensile strength tests were conducted on various mortar mixtures for different curing times. The results indicate that in the presence of a mineral mixture of fly ash and GGBS, the rheological behavior of paste and mortar is similar. Compared with OPC-GGBS-based mixtures, both cement with fly ash and ternary mixtures show less shear resistance or impact resistance. The rheological behavior of the mortar also matches the rheological behavior in the flow table test. Therefore, it is easy to use the vane shear test equipment to conduct cohesion studies to understand the properties of cement paste and mortar using mineral admixtures. The strength results show that the long-term strength of GGBS-based mixtures and ternary mixed mixtures is better than that of fly-ash-based mixtures. For all mixtures, the strength characteristics are greatest at a w/b ratio of 0.6. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.